Digestibility, ruminal enzyme activity, fermentation characteristics, and selected blood biochemical parameters in calves supplemented with humic acid - Abouamra, Waleed K.; Amhabj, Abdelslam M. A.; Tawfik, Hamdan M.; Ayad, Ahmed A.; Farghaly, Mohsen M.; Monzaly, Hayam M. A.; Khormi, Mohsen A.; Taha, Ramadan; Ahmed, Ahmed Ezzat; Hajri, Amira K.; Albalawi, Marzough Aziz; Ali, Montaser Elsayed (Frontiers in Veterinary Science, 2026)
This study aimed to evaluate the effect of humic acid (HA) on growth performance, nutrient digestibility, ruminal fermentation, ruminal enzyme activity, and certain blood biochemical parameters. A total of 45 calves (11 ± 0.25 months of age; 280 ± 5.55 kg BW) were divided equally into three groups. The control group received a basal diet composed of a concentrate feed mixture (CFM) with roughage. The treatment groups received the same basal diet supplemented with 1 and 2% humic acid in the CFM, respectively. The study revealed that the treatment groups had significantly lower total dry matter (DM) intake (p = 0.029). The treatment groups showed higher (p = 0.013) ether extract (EE) digestibility and digestible crude protein (DCP) (p = 0.001) than the CFM group. However, ammonia nitrogen (NH3-N, mg/100 mL) was significantly lower (p = 0.012) in the 1% HA and 2% HA groups compared to the CFM group. The 2% HA group had significantly higher (p = 0.001) proportions of acetate and propionate compared to the 1% HA and CFM groups. The treatment groups had significantly higher (p = 0.001) α-amylase, lipase, urease, and protease activities compared to the CFM group. In addition, the concentration of total soluble protein in the rumen liquid was higher (p = 0.006) in the 1% HA group compared to the CFM group. The 2% HA group had higher (p = 0.049) glucose concentrations than the CFM group. In conclusion, humic acid supplementation at 1% or 2% may improve nutrient digestibility and ruminal fermentation efficiency, enhance enzyme activity, and support normal blood profiles in calves.